Evaluation of the Access Bio CareStart rapid SARS-CoV-2 antigen test in asymptomatic individuals tested at a community mass-testing program in Western Massachusetts - Sara Suliman; Wilfredo R. Matias; Isabel R. Fulcher; Francisco J. Molano; Shannon Collins; Elizabeth Uceta; Jack Zhu; Ryan M. Paxton; Sean F. Gonsalves; Maegan V. Harden; Marissa Fisher; Jim Meldrim; et al. (Scientific Reports, 2022)
Abstract Point-of-care antigen-detecting rapid diagnostic tests (RDTs) to detect Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) represent a scalable tool for surveillance of active SARS-CoV-2 infections in the population. Data on the performance of these tests in real-world community settings are paramount to guide their implementation to combat the COVID-19 pandemic. We evaluated the performance characteristics of the CareStart COVID-19 Antigen test (CareStart) in a community testing site in Holyoke, Massachusetts. We compared CareStart to a SARS-CoV-2 reverse transcriptase quantitative polymerase chain reaction (RT-qPCR) reference, both using anterior nasal swab samples. We calculated the sensitivity, specificity, and the expected positive and negative predictive values at different SARS-CoV-2 prevalence estimates. We performed 666 total tests on 591 unique individuals. 573 (86%) were asymptomatic. There were 52 positive tests by RT-qPCR. The sensitivity of CareStart was 49.0% (95% Confidence Interval (CI) 34.8–63.4) and specificity was 99.5% (95% CI 98.5–99.9). Among positive RT-qPCR tests, the median cycle threshold (Ct) was significantly lower in samples that tested positive on CareStart. Using a Ct ≤ 30 as a benchmark for positivity increased the sensitivity of the test to 64.9% (95% CI 47.5–79.8). Our study shows that CareStart has a high specificity and moderate sensitivity. The utility of RDTs, such as CareStart, in mass implementation should prioritize use cases in which a higher specificity is more important, such as triage tests to rule-in active infections in community surveillance programs.